2005
DOI: 10.1007/s11064-005-2748-3
|View full text |Cite
|
Sign up to set email alerts
|

Role of cAMP-Dependent Protein Kinase on Acute Picrotoxin-Induced Seizures

Abstract: cAMP-dependent protein kinase (PKA) is a major modulator of synaptic transmission likely to be involved in molecular and cellular events leading to epileptogenesis, but little is known about how it affects the onset of acute epileptic seizures. In this study, we determined PKA enzymatic activity in the rat hippocampus during picrotoxin-induced seizures, using H-9 dihydrochloride, a PKA inhibitor, to investigate the in vivo effects of this enzyme on seizures induced by picrotoxin microdialysis in the rat hippoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 27 publications
(38 reference statements)
2
16
1
Order By: Relevance
“…Third, inhibition of PKA by KT 5720 and Rp-cAMPS significantly reduced but not completely blocked CRF-induced increases in epileptiform activity. In accordance with our results, tremendous evidence demonstrates that AC/cAMP/PKA pathway plays a facilitatory role in epilepsy [53], [54], [55], [56], [57], [58].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Third, inhibition of PKA by KT 5720 and Rp-cAMPS significantly reduced but not completely blocked CRF-induced increases in epileptiform activity. In accordance with our results, tremendous evidence demonstrates that AC/cAMP/PKA pathway plays a facilitatory role in epilepsy [53], [54], [55], [56], [57], [58].…”
Section: Discussionsupporting
confidence: 93%
“…Because CRF 2 receptors are coupled to AC/cAMP/PKA pathway and there is strong evidence demonstrating that cAMP and PKA signals exert a tonic control of epilepsy [53], [54], [55], [56], [57], [58], we tested the roles of this pathway in CRF-mediated facilitation of epileptiform activity. Slices were pretreated with the selective AC inhibitor MDL 12330A (50 µM) for ∼20 min and the same concentration of MDL 12330A was included in the PTX-containing extracellular solution and applied in the bath before and during the application of CRF.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, cPKA is involved in controlling hippocampal neuronal activity, [1][2][3][4] and has been reported to participate in maintaining epileptic activity and inducing status epilepticus. [5][6][7][8][9][10] For instance, in tottering mice 5 or genetically prone to audiogenic seizures (GPAS) rats, 6 the abnormal elevation of PKA activity has been demonstrated to contribute to a functional impairment of GABA A receptor, and be involved in mechanisms of genetic predisposition to spontaneous seizures. In status epilepticus (SE) model, Niimura et al 7 observed that phosphorylation of NR1 by PKA was depressed relative to controls immediately following SE and transiently increased above control values upon the termination of SE.…”
Section: Introductionmentioning
confidence: 99%
“…The general mechanisms proposed for the interaction of pulse‐modulated RF signals with the central nervous system (CNS) are controversial, and include alteration of Ca 2+ efflux in vivo (Adey et al, 1982; Paulraj et al, 1999) but no effect on rat brain tissues exposed in vitro (Shelton and Merritt, 1981; Merritt et al, 1982), low‐level exposure‐induced increases in blood–brain barrier (BBB) permeability and neuronal damage (Salford et al, 2003) but no changes in the vascular barrier (Finne et al, 2002, 2006), and an increase in regional cerebral blood flow (Huber et al, 2005). In this regard, both in vitro experiments (Beason and Semm, 2002; Barteri et al, 2005; Zhao et al, 2007) and in vivo experiments in animals (Dubreil et al, 2003; Paulraj and Behari, 2004; Lopez‐Martín et al, 2006) and humans (Maby et al, 2006) have reported biological effects after acute GSM‐900 exposure. Many of the responses described have been interpreted as secondary to a variety of cellular signal transduction pathways and gene expression responses (Belyaev et al, 2006), such as heat shock responses (Cotgreave, 2005).…”
mentioning
confidence: 99%